Bimetallic zeolite-imidazole framework-based heterostructure with enhanced photocatalytic hydrogen production activity. Issue 16 (1st March 2021) - Arif, Nayab; Lin, Ye-Zhan; Wang, Kai; Dou, Yi-Chuan; Zhang, Yu; Li, Kui; Liu, Shiquan; Liu, Fu-Tian
Abstract : The g-C3 N4 -MoS2 could facilitate the separation as well as utilization efficiency of the photo-generated charge carriers in the ZnM-ZIFs, and hence improved the photocatalytic H2 production with and without sacrificial agent. Abstract : Bimetallic zeolite-imidazole frameworks with controllable flat band position, band gap and hydrogen evolution reaction characteristics were adopted as a photocatalytic hydrogen production catalyst. Furthermore, the g-C3 N4 –MoS2 2D–2D surface heterostructure was introduced to the ZnM-ZIF to facilitate the separation as well as utilization efficiency of the photo-exited charge carriers in the ZnM-ZIFs. On the other hand, the ZnM-ZIFs not only inhibited the aggregation of the g-C3 N4 –MoS2 heterostructure, but also improved the separation and transport efficiency of charge carriers in g-C3 N4 –MoS2 . Consequently, the optimal g-C3 N4 –MoS2 –ZnNi-ZIF exhibited an extraordinary photocatalytic hydrogen evolution activity 214.4, 37.5, and 3.7 times larger than that of the pristine g-C3 N4, g-C3 N4 –ZnNi-ZIF and g-C3 N4 –MoS2, respectively, and exhibited a H2 -evolution performance of 77.8 μmol h −1 g −1 under UV-Vis light irradiation coupled with oxidation of H2 O into H2 O2 . This work will furnish a new MOF candidate for photocatalysis and provide insight into better utilization of porous MOF-based heterostructures for hydrogen production from pure water.